Drivers of Investment Accelerations - Jakob de Haan; Kersten Stamm; Shu Yu (CESifo GmbH, 2024)
Following earlier studies on accelerations of output and the capital stock, we propose an adjusted method to identify accelerations in investment that ensures that the identified episodes are characterized by sustained increases in per capita investment growth to a relatively high rate. We identify 192 investment accelerations in 93 economies (34 advanced economies and 59 emerging and developing economies) over 1950-2022. Our evidence suggests that economic policy reform and institutional quality are important drivers of the likelihood that such an acceleration occurs. Furthermore, we find that the impact of reform on this likelihood is conditioned by institutional quality.
Keywords: E22; O11; O43; 330; investment accelerations; institutional quality; policy reform governance